Implementation of home visit method in offline learning during the Covid-19 pandemic - Benjamin Metekohy; Novita Sahertian; David Ming (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
Learning during the pandemic, based on government policies through the Ministry of Education and Culture, has issued a Circular Letter of the Ministry of Education and Culture (Kemendikbud) No. 4 of 2020 regarding the implementation of education policies in the emergency period of the spread of Corona Virus Disease (Covid-19). In the field of education, make a learning system in such a way as to prevent the spread of Covid-19. For this reason, online learning certainly has obstacles in its implementation. Online learning requires teachers, parents, and students to be able to use the internet. So that not a few schools carry out offline learning, previously all educational institutions conducted offline learning by giving assignments to students as a substitute for studying at school. Offline learning activities like that require parents to be able to guide their children in learning, understanding the material and completing school assignments given. This is an obstacle for offline learning with a task assignment system. Many parents are busy with other activities so they don't have much time to supervise and replace the teacher's position in guiding their children to study. In the era of the COVID-19 pandemic, the teaching and learning process that should take place in a classroom or school must be replaced by studying at home. This paper was written to address the following problems. What is the home visit method in offline learning? Is the Home visit method an alternative to learning during the Covid-19 pandemic? What are the indicators, objectives and benefits of the home visit method in offline learning?